Kansas Irrigation Leases - Langemeier, Larry N. (My University, 1995)
This publication illustrates crop-share irrigation lease inputs and costs for center-pivot and flood-irrigation systems.
MF284_1995_10
Keywords: MF284; Livestock; Economics; MF